Posted by **Rob** on Sunday, August 24, 2008 at 7:50pm.

Given f(x)=2x^3-7 find f^-1(x) and then find f^-1(-2)

I though that this meant inverse function.

x=2y^3-7

x+7=2y^3

(x+7)/2=y^3

((x+7)/2)^(1/3)=y

so this meant f^-1(-2) = 1.35721

The professor posted the answer as being 6. I'm not sure if I misunderstood the question or if I'm completely off in my answer.

Any ideas?

thanks

- calculus -
**bobpursley**, Sunday, August 24, 2008 at 8:34pm
It looks correct to me

## Answer This Question

## Related Questions

- math - The cost of producing q articles is given by the function C=f(q)=100+2q...
- health and social - 1.what is meant by health and well-being? 2. what is meant ...
- math - Could you show me step by step how to find the inverse of this problem: ...
- Pre-Calculus - Find the inverse function for the function f(x)=2^(x)+1/2^(x)-1 ...
- Pre-calculus - Given the following values for f(t): t : f(t) 3 : -7 6 : 6 9 : 19...
- Functions - math - The function f is such that f(x) = 2x + 3 for x ? 0. The ...
- Math - Given P (x) = x-1/ 2x-3, Find P (-2) The notation P(-2) for your given P(...
- math - simplify -cd^-4e^-1 okay rob or jim. read my math tip notes, okay? ...
- pre calculus - Find the inverse of the function below. Graph the function below ...
- math-calculus - 1.For any function y+f(x), express dy/dx using limit notation. ...

More Related Questions